2019
DOI: 10.2147/cmar.s209861
|View full text |Cite
|
Sign up to set email alerts
|

<p>Columbamine suppresses the proliferation and malignization of colon cancer cells via abolishing Wnt/β-catenin signaling pathway</p>

Abstract: BackgroundColon cancer is one of the most common malignancies worldwide. Because of the side effects and defects in tolerance of chemotherapy, it is necessary to discover new drugs for colon cancer treatment. Columbamine has been identified as an effective anti-osteosarcoma compound with only minor side effects. In this study, we analyzed the anticancer effect of columbamine on colon cancer.MethodsHuman colon cancer cell lines were treatment with columbamine. MTT assay, colony formation assay, apoptosis detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…The previous report showed that Columbamine suppressed colon cancer cells via blocking Wnt/β-catenin signaling pathway. 12 Lin et al found that Columbamine inhibited hepatocellular carcinoma cells via abolishing of PI3K/AKT, p38 and, ERK1/2 MAPK signaling pathways. 13 Columbamine prevented the development of metastatic osteosarcoma U2OS cells with low cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous report showed that Columbamine suppressed colon cancer cells via blocking Wnt/β-catenin signaling pathway. 12 Lin et al found that Columbamine inhibited hepatocellular carcinoma cells via abolishing of PI3K/AKT, p38 and, ERK1/2 MAPK signaling pathways. 13 Columbamine prevented the development of metastatic osteosarcoma U2OS cells with low cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Columbamine prevented the growth and deterioration of colon cancer by blocking the Wnt/β-catenin signaling pathway. 12 Columbamine also inhibits hepatocellular carcinoma development by preventing AKT and ERK1/2 signaling pathways. 13 Meanwhile, Columbamine has a cytotoxic effect on osteosarcoma cells to inhibit tumor development.…”
Section: Introductionmentioning
confidence: 99%
“…Columbamine exerts antiproliferative, anti-metastasis, anti-vasculogenic, and cytotoxic effects in various cancer types, including human CRC, HCC, and metastatic osteosarcoma ( Zhang et al, 2014 ; Lei et al, 2019 ). Columbamine significantly decreases tumor volumes in HCT116 or SMMC7721 xenograft mouse model, as well as induces cell apoptosis and G 2 /M phase arrest via Wnt/β-catenin, MAPK, CDK6, STAT3 signaling pathways in in vitro models ( Lin et al, 2019 ).…”
Section: Antitumor Effects and Corresponding Mechanismsmentioning
confidence: 99%
“…EMT typically initiates metastasis during cancer progression, during which epithelial cells acquire migration and invasion characteristics, and MMPs' expression increases, with the loss of E-cadherin and gain of N-cadherin and Vimentin [54][55][56]. β-catenin is an EMT marker and a core factor of the Wnt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%